PENERAPAN ALUR TAK TERHINGGA DALAM FILM PENDEK FIKSI UNTITELED - I Putu Adi Sanjaya; I Wayan Mudra; Ni Kadek Dwiyani (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
The author took the Independent Study/Project option in the MBKM program lectures in one semester. The writer chooses a concept related to the world of film. This program is carried out at the Sri Redjeki Films Studio, which has produced various types of films, ranging from documentaries to fiction. The selection of the Sri Redjeki Films Studio aims to add insight in producing an audio-visual work in creating works that have a novelty.The purpose of this research is to explain the plot in a short film entitled Untilited. The theory used in this application is the Simulacra theory and the concept of Infinite Plot. Data obtained through observation, interviews and documentation. The results of the study show that there are 8 types of plots in Untilited films, namely: Forward Plot, Backward Plot, Mixed Plot, Spotlight Plot, Climax Plot, Anti-climactic Plot, Chronological Plot, and Infinite Plot. In this writing, infinite plot is the concept applied. as the main concept. In addition, Simulacra Theory and Fiction Film Theory are applied in the Untitled film as the main theory. In conclusion, not all categories in the plot are applied in the Untitled film. This film makes the audience's expectations change repeatedly. The concepts and theories used are in line with the plot applied in the short film entitled Untitled.